Teacher learning to teach mathematics via reasoning and proving: a discursive analysis of lesson plans modifications - Weingarden, Merav; Buchbinder, Orly (Frontiers in Education, 2023)
Despite the importance of reasoning and proving in mathematics and mathematics education, little is known about how future teachers become proficient in integrating reasoning and proving in their teaching practices. In this article, we characterize this aspect of prospective secondary mathematics teachers' (PSTs') professional learning by drawing upon the commognitive theory. We offer a triplelayer conceptualization of (student) learning, teaching, and learning to teach mathematics via reasoning and proving by focusing on the discourses students participate in (learning), the opportunities for reasoning and proving afforded to them (teaching), and how PSTs design and enrich such opportunities (learning to teach). We explore PSTs' pedagogical discourse anchored in the lesson plans they designed, enacted, and modified as part of their participation in a university-based course: Mathematical Reasoning and Proving for Secondary Teachers. We identified four types of discursive modifications: structural, mathematical, reasoning-based, and logic-based. We describe how the potential opportunities for reasoning and proving afforded to students by these lesson plans changed as a result of these modifications. Based on our triple-layered conceptualization we illustrate how the lesson modifications and the resulting alterations to student learning opportunities can be used to characterize PSTs' professional learning. We discuss the affordances of theorizing teacher practices with the same theoretical lens (grounded in commognition) to inquire student learning and teacher learning, and how lesson plans, as a proxy of teaching practices, can be used as a methodological tool to better understand PSTs' professional learning.